2015
DOI: 10.1111/jpm.12209
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia through the carers' eyes: results of a European cross‐sectional survey

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. Accessible summary• Schizophrenia is a serious mental disorder affecting approximately 29 million people worldwide. The ideal treatment and care of patients with schizophrenia should be provided by a multidisciplinary 'team' involvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
2
10
0
1
Order By: Relevance
“…Most family carers in this study mentioned the limited effectiveness of antipsychotic medication, which was unsurprising since numerous studies have drawn attention to this issue (Gotzsche, Young & Crace, ; Khin et al, ; Leucht, Arbter et al., 2009; Leucht, Corves et al., 2009; Morrison, Meehan & Stomski, , b). Despite noting the lack of marked benefits that resulted from the use of antipsychotic medication, the family carers in our study noted that the positive effects outweighed the negative effects, which was broadly consistent with the findings of a European survey of carers (Svettini et al, ). Nonetheless, the findings of this study suggest that clinicians overly relied on medications, and perhaps could consider alternative treatment approaches.…”
Section: Discussionsupporting
confidence: 90%
“…Most family carers in this study mentioned the limited effectiveness of antipsychotic medication, which was unsurprising since numerous studies have drawn attention to this issue (Gotzsche, Young & Crace, ; Khin et al, ; Leucht, Arbter et al., 2009; Leucht, Corves et al., 2009; Morrison, Meehan & Stomski, , b). Despite noting the lack of marked benefits that resulted from the use of antipsychotic medication, the family carers in our study noted that the positive effects outweighed the negative effects, which was broadly consistent with the findings of a European survey of carers (Svettini et al, ). Nonetheless, the findings of this study suggest that clinicians overly relied on medications, and perhaps could consider alternative treatment approaches.…”
Section: Discussionsupporting
confidence: 90%
“…The majority of carers interviewed were parents of a person with schizophrenia, with a gender bias in the sample, such that around three quarters of participants were female. However, this is in line with the gender balance found in other convenience samples of carers of persons with schizophrenia [46], and reflects the fact that mothers are most frequently the primary carer in schizophrenia [47]. It is possible that spouses, siblings, or children (or those of a younger age in general) may have different perceptions of what the important outcomes are.…”
Section: Discussionsupporting
confidence: 70%
“…It is common for carers to simultaneously hold both positive and negative attitudes towards medication which could further influence the attitudes of a family member with mental illness. For example, a European survey of carers of patients with schizophrenia showed that most carers recognized the importance of medication to help patients get better (76%) while at the same time believing it damages their general health (67%; Svettini et al, 2015). Such concerns are legitimate given the heightened health risks associated with many antipsychotic medications (e.g., weight gain, new onset diabetes).…”
Section: Discussionmentioning
confidence: 99%